Prinsip Komunikasi Al-Qur’an Dalam Menghadapi Era Media Baru - Isman Iskandar (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2019)
This research seeks to reconstruct the communication terms in the Qur'an with a more holistic approach. The existing terms all reinforce each other and form a configuration of meanings for the major themes of Islamic communication. At least four domains of Islamic mass media; da'wah, tabligh, amar ma'ruf nahi mungkar and morality (communication, information, change and development, and wisdom). The analysis of key concept communication gave birth to the principle of communication in the face of new media extracted from the values ​​of the Qur'an. The principle is then elaborated in the form of: 1) Communicating in a good way and message 2) Honesty of information and reasonableness 3) Verification of information and responsibility, 4) Inviting to the path of God (Islam) and or contrasting with the best way 5) Anticipating communication disorders and violations.